Effectiveness of Conceptual Change Text in Reducing Acid-Base Misconceptions - Rosyidah Syafaatur Rohmah; Irma Ayu Virtayanti (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2021)
Students had difficulty understanding the acid-base concept because of its complex nature. This difficulty could lead to an acid-base misconception. One of the learning tools that can be used to overcome misconceptions was Conceptual Change Text. This study aimed to determine the effectiveness of the Conceptual Change Text in reducing acid-base misconceptions. This study used one group pre-test post-test design with 18 Basic Chemistry II students at Billfath University. An acid-based diagnostic test determined students' misconceptions. The results showed there are nine and one misconceptions in pre-test and post-test, respectively. The application of the Conceptual Change Text was successful in reducing acid-base misconceptions with an effectiveness percentage of 97.76%.